Environmental entrepreneurship markets meet the environment in unexpected places - Huggins, Laura E.; Edward Elgar Publishing (Cheltenham : Edward Elgar Pub. Ltd., 2013)
In this innovative book, Laura E. Huggins finds path breaking entrepreneurial solutions to difficult environmental challenges in some of the world's poorest areas. The approaches entrepreneurs are taking to these challenges involve establishing property rights and encouraging market exchange. From beehives to barbed wire, these tools are creating positive incentives and promoting both economic development and environmental improvements. The case studies are from the developing world and reveal where the biggest victories for less poverty and more conservation can be won. The pursuit begins by learning from local people solving local problems. Environmental Entrepreneurship encourages a broad audience to consider secure property rights and free markets as key ingredients to moving out of poverty and improving environmental quality at the same time. It will appeal to academics and students of environmental studies, environmental economics, environmental policy, as well as international development and business. Entrepreneurs and environmental groups such as The Nature Conservancy, Conservation International, and The World Resources Institute will also find a wealth of invaluable information in this book.
1. Markets meet the environment in unexpected places -- 2. Saving wildlife in Kenya and Sub-Sahran Africa / with Shawn Regan and Terry Anderson -- 3. Fencing fisheries in Nambia and beyond -- 4. Ecosystems at your service in South America -- 5. The thirsty dragon -- 6. Un-American Indian reservations and resource management / with Terry Anderson and Laura Huggins.
Includes index.
Keywords: Social entrepreneurship; Economic development; Sustainable development; Markets; Electronic books